Representation of Women's Struggles in the Film Gadis Kretek Using Semiotic Analysis: Representasi Perjuangan Perempuan dalam Film Gadis Kretek Menggunakan Analisis Semiotik - Sari, Dea Puspita; Febriana, Poppy (House of Wisdom: Journal on Library and Information Sciences, 2025)
General Background: Film, as a powerful mass medium, shapes public views by conveying messages through audio and visual elements. The representation of women in media is a crucial area of study, reflecting societal norms and power dynamics. Specific Background: The Indonesian film "Gadis Kretek" offers a narrative rich with the struggles of women within the traditional kretek industry, addressing pervasive issues of gender inequality and patriarchal ideology. Knowledge Gap: While the film has received significant attention, a detailed semiotic analysis of its portrayal of women's struggles against patriarchal structures remains underexplored. Aims: This study aims to analyze the representation of women in "Gadis Kretek" using John Fiske's semiotic framework, examining the levels of reality, representation, and ideology. Results: The analysis reveals that the film represents women's fight against patriarchal domination, evidenced by their limited roles and exclusion from key decision-making processes. Novelty: This research provides a unique and in-depth semiotic reading of the film, illuminating its ideological message on female empowerment and resilience. Implications: The findings underscore the film's role as a medium for social commentary, emphasizing the importance of women's self-awareness and empowerment to overcome inequality and achieve their ambitions within male-dominated industries. Highlights : The study analyzes the representation of women's struggles using John Fiske's semiotic analysis. The film depicts gender inequality through women's limited roles and male-dominated decision-making. The research highlights the film's ideological message on the importance of women's empowerment in the face of patriarchy. Keywords: Semiotics, Female Representation, Gadis Kretek, Patriarchy, Kretek Industry